1999
DOI: 10.1209/epl/i1999-00409-9
|View full text |Cite
|
Sign up to set email alerts
|

Failure time and microcrack nucleation

Abstract: The failure time of samples of heterogeneous materials (wood, fiberglass) is studied as a function of the applied stress. It is shown that in these materials the failure time is predicted with a good accuracy by a model of microcrack nucleation proposed by Pomeau. It is also shown that the crack growth process presents critical features when the failure time is approached.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
95
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 12 publications
14
95
0
Order By: Relevance
“…In fig.12c (reproduced in fig.10 for the sake of clearness), E measured when a constant pressure is applied to the sample is plotted as a function of τ −t τ . A power law is found in this case too [21]. The exponent γ is, within error bars, the same in the three cases.…”
Section: The Dependence Of γ On the Load Featuressupporting
confidence: 68%
See 2 more Smart Citations
“…In fig.12c (reproduced in fig.10 for the sake of clearness), E measured when a constant pressure is applied to the sample is plotted as a function of τ −t τ . A power law is found in this case too [21]. The exponent γ is, within error bars, the same in the three cases.…”
Section: The Dependence Of γ On the Load Featuressupporting
confidence: 68%
“…The global results of the measurements are the following: a list of the positions of microcracks, the strain of the samples and the energy released as a function of the control parameter P . Further details of the setup are described elsewhere [10,9,21,22]. …”
Section: High Pressure Chambers (Hpc)mentioning
confidence: 99%
See 1 more Smart Citation
“…When a constant stress is applied to a solid, it will eventually break, even if the applied stress is below the experimental breaking threshold [1][2][3][4][5][6][7]. This phenomenon is known as subcritical rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Considering previous studies where a large number of worldwide observations was used (Bufe and Varnes 1993;Bowman et al 1998;Papazachos and Papazachos 2001;Papazachos et al 2005, among many others), theoretical considerations and laboratory results (Rundle et al 1996;Ben-Zion et al 1999;Guarino et al 1999;Rundle et al 2000;Ben-Zion and Lyakhovsky 2002), as well as stress transfer considerations (Mignan et al 2007), a typical value for exponent m equal to 0.3 was adopted in the present study. Bowman et al (1998) suggested the minimization of a curvature parameter, C, which is defined as the ratio of the root mean square error of the power law fit (relation 1) to the corresponding linear fit error.…”
Section: Introductionmentioning
confidence: 99%